The Effect of Post-discharge Telephone Follow-Up on the Inherent Dignity of Patients with Heart Failure - Tahereh Nikkhah; Hossein Bagheri; Mahboubeh Khajeh; Ahmad Khosravi (Hamadan University of Medical Sciences, 2021)
Introduction: After being discharged, patients with heart failure, are exposed to the problems of disease management in the family and community, and follow-up interventions after discharging can play a significant supportive role in promoting a sense of worth in them. The purpose of this study was to investigate the effect of post-discharge telephone follow-up on the inherent dignity of patients with heart failure. Materials and Methods: In this randomized clinical trial, 70 patients with heart failure referred to cardiac and cardiac care units of a hospital in an urban area of Iran were selected and assigned into two intervention and control groups using the block randomization with block size of 4. The intervention group was followed up by telephone for one month once a week with regard to drug use, symptoms, daily activities, and type of nutrition. The patients' inherent dignity was assessed using the Inherent Dignity Questionnaire (IDQ) before and after one month of the intervention. Data were analyzed using the SPSS 16. Results: In this study, 70 patients with heart failure were compared in two groups of intervention and control with mean and standard age deviation of 65±10.68, and 67±13.31 years (P꞊0.46). Independent t-test showed a statistically significant difference between the groups in the mean score difference of intrinsic dignity (0.8±0.3 and 0.07±0.2, respectively), before and after the intervention (P<0.001). Conclusion: According to the results of the present study, which showed that post-discharge telephone follow-up improves the inherent dignity of patients, therefore, to maintain and promote the inherent dignity of patients with heart failure in the community, planned and systematic post-discharge follow-ups are recommended.